Reverberations of a common encounter. Domitila, Marielle, Daniela, Albertina and Lucía: Their voices in oursspañol - Alvarez, María Belén; Elgueta, Ana Claudia; Mehl, Larissa; Monteiro, Polliana; Olaiz, María Alejandra (Facultad de Ciencias Políticas y Sociales, 2020)
In this work we propose to approach the stories of five Latin American women, interpreting their absence, their deaths, like a silencing attempt. These women make it possible for us to think about the place and the forms that the rights manifest and the violence in our territories. At the same time, the categories of "necropolitics" and "intersectionality" help us connect textualities with the purpose of visibility into the continuum of oppressions and possible forms of resistance.